NEW TRENDS IN LOCAL AND INTERNATIONAL BUSINESS FOR ELECTRICAL AND ELECTRONICS ENGINEERS IN 2025 - Dr. Pravin R. Choube; Prof. S. C. Mhamane (Ecominds Press, 2025)
Electrical and electronics engineering (EEE) is a field experiencing rapid transformations in both local and international business environments. The growing demands for sustainable energy solutions, smart technologies, and digital transformation are reshaping the industry. This paper explores emerging trends in EEE that are influencing business strategies for engineers globally in 2025. Key trends include the integration of renewable energy technologies, the rise of smart cities and IoT (Internet of Things), advancements in automation and robotics, and the increasing importance of sustainability and energy efficiency. The paper provides insights into how engineers are adapting to these trends through innovation, technology, and market strategies. Moreover, the role of artificial intelligence (AI), blockchain, and digital twins in EEE business models will be examined. This paper discusses the implications of these trends for the future of electrical and electronics engineers in the competitive global market.
Keywords: Electrical Engineering, Electronics, Business Trends, Renewable Energy, Automation, Sustainability, Smart Cities, Internet of Things (IoT), Artificial Intelligence (AI).